The Effectiveness Of FLACC Pain Scale Assessment Education Through Zoom Media On The Assessment Skills Of ICU Nurses - TEGUH WICAKSONO; PUGUH RAHARJO; RENY TRI FEBRIANI (PROFESSIONAL HEALTH JOURNAL, 2026)
Pain assessment is a critical aspect of delivering quality care, particularly in intensive care units (ICU). Undetected and poorly managed pain can negatively impact patient recovery. One of the commonly used pain assessment methods for non-verbal patients is the FLACC scale (Face, Legs, Activity, Cry, Consolability). This study aims to evaluate the effectiveness of FLACC pain assessment education through Zoom media on the assessment skills of ICU nurses at Kapuas B RSUD Dr. Saiful Anwar, East Java Province. The research employs a quantitative approach with a pre-experimental design using the one-group pretest-posttest design. The sample consists of 27 ICU nurses selected through total sampling. The results showed that before the education intervention, most nurses (74.1%) were deemed incompetent in pain assessment skills. After the intervention, the majority of nurses (85.2%) were assessed as competent. Statistical analysis using the Wilcoxon test indicated a significant difference in assessment skills before and after the education intervention (Z = -4.000; Asymp. Sig. = 0.000). These findings demonstrate that providing education through Zoom is effective in improving the assessment skills of nurses in using the FLACC scale to evaluate patient pain in the ICU. Continuous education for healthcare professionals, particularly ICU nurses, is crucial to enhance pain assessment skills and support optimal patient care. Online education methods, such as via Zoom, prove to be an efficient alternative in certain circumstances.